Does intellectual capital efficiency explain corporate social responsibility engagement-firm performance relationship? Evidence from environmental, social and governance performance of US listed firms - Faisal Shahzad; Mushahid Hussain Baig; Ijaz Ur Rehman; Asif Saeed; Ghazanfar Ali Asim (Borsa İstanbul Review, 2022)
This paper examines the effect of corporate social responsibility on firm performance by accounting for the role of Intellectual capital efficiency as a mechanism underlying Corporate Social Responsibility (CSR)- firm performance association. In this study, we consider 2132 US companies and develop a structural model for CSR, Intellectual Capital (IC), and firm performance while contemplating endogeneity issues in analyses over the period of 2009-2018. The value-added intellectual capital co-efficient is employed as a proxy measure for IC performance, taking into consideration corporate performance and governance measures. The findings suggest that CSR has a significant effect on firm performance. In particular, the findings reveal that CSR has a link with IC, indirectly affecting a firm performance, and the association between CSR and firm performance is partially mediated by Intellectual capital efficiency.
Keywords: A25; M14; O34; 330; Firm performance; Corporate social responsibility; Intellectual capital efficiency